2016
DOI: 10.1016/j.ijid.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of supplementary immunization activities on the epidemiology of measles in Tianjin, China

Abstract: Summary Objectives China has repeatedly used supplemental immunization activities (SIAs) to work towards measles elimination, but it is unknown if the SIAs are reaching non-locals, migrants from rural to urban areas. This study characterizes temporal trends in measles incidence by local and non-local residency and evaluates the impact of SIAs on measles incidence in Tianjin, China. Methods Daily measles case counts were tabulated separately by residency. These two datasets were combined so that each day had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…Similar to the results of many other studies, the significant increase of the incidence of measles was mainly due to the high incidence of measles among migrants with low vaccine coverage [ 10 – 13 ]. The incidence of measles in migrants was several times higher than that of local residents in recent years in the Jing’an District.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to the results of many other studies, the significant increase of the incidence of measles was mainly due to the high incidence of measles among migrants with low vaccine coverage [ 10 – 13 ]. The incidence of measles in migrants was several times higher than that of local residents in recent years in the Jing’an District.…”
Section: Discussionsupporting
confidence: 86%
“…At 3 months of age, almost all infants lack a protective titer of maternal antibodies, regardless of the antibody titer in their mothers. These findings are important because Tianjin has struggled with measles control in the context of China's larger elimination efforts, despite near universal immunization coverage among young children [25,26] and the completion of 2 major supplementary immunization activities in the past 10 years, which have each targeted hundreds of thousands of children for vaccination [27]. With administration of the initial measles dose at 8 months of age, China's immunization program attempts to strike a balance between immunizing at earlier ages to provide protection to these infants, who form an increasing proportion of all case patients, and the poorer immune response elicited at earlier ages [15].…”
Section: Discussionmentioning
confidence: 99%
“…Data from 2012 were not available, but we did find significantly lower rates of measles in 2013 and 2014 compared to 2009. However, the resurgence in cases in 2015 points to the difficulty and the necessity of maintaining a cohort that is fully immunized against this highly infectious disease: a study of measles in Tianjin, China, also found that rates of disease bounced back within 2 to 4 years of an SIA [ 30 ]. The coverage of the second dose of measles vaccine in Afghanistan is only estimated to be around 60% as of 2015 [ 25 ].…”
Section: Discussionmentioning
confidence: 99%